2012
DOI: 10.1007/s12033-012-9612-x
|View full text |Cite
|
Sign up to set email alerts
|

With or Without Sugar? (A)glycosylation of Therapeutic Antibodies

Abstract: Antibodies and antibody-based drugs are currently the fastest-growing class of therapeutics. Over the last three decades, more than 30 therapeutic monoclonal antibodies and derivatives thereof have been approved for and successfully applied in diverse indication areas including cancer, organ transplants, autoimmune/inflammatory disorders, and cardiovascular disease. The isotype of choice for antibody therapeutics is human IgG, whose Fc region contains a ubiquitous asparagine residue (N297) that acts as an acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 137 publications
1
47
0
2
Order By: Relevance
“…ADCC efficacy of IgG antibodies is significantly dependent on Fc glycosylation patterns (34). The absence of fucose on N297 of mAbs can results in conformational changes in the Fc region and increase ADCC by increasing the affinity between the Fc region and Fcg receptors (27,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…ADCC efficacy of IgG antibodies is significantly dependent on Fc glycosylation patterns (34). The absence of fucose on N297 of mAbs can results in conformational changes in the Fc region and increase ADCC by increasing the affinity between the Fc region and Fcg receptors (27,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined the Asn to Gly (N297G) variant, along with Asn to Ala (N297A), impact on Fc␥R binding and pharmacokinetics for the first time and concluded that N297G and N297A variants have similar pharmacokinetics (PK) to that of the wild type antibodies (14). Aglycosylated antibodies have a very low levelof binding to Fc␥Rs (15,16). The advantage with this approach is that it requires a single mutation in the constant domain (CH2), thus minimizing the risk of immunogenicity via the formation of new epitopes.…”
Section: Edited By Peter Cresswellmentioning
confidence: 99%
“…Carbohydrate groups participate in the integrity of most biologics by reducing aggregation propensity, increasing solubility, stabilizing the native conformation, protecting against various degradation pathways (hydrolysis, oxidation) and overall stabilizing the macromolecules. 28,55 This functionality is particularly relevant for antibodies as all IgGs are naturally N-glycosylated at position N297 in each of the CH2 chains of the Fc domain. It has been demonstrated on several occasions that this N-glycan participates in the stabilization of mAbs against aggregation caused by various stresses.…”
Section: Discussionmentioning
confidence: 99%
“…8,24,26,27,56,57 Natural IgGs present in human serum are all glycosylated in the Fc domain whereas only less than a third are glycosylated in the Fab domain. 55 N-glycans are found attached to the variable region of the LC, the HC or both. It is estimated that »20% of the variable region of mAbs bear an N-glycosylation site motif.…”
Section: Discussionmentioning
confidence: 99%